Inner-city women at risk for cervical cancer: Behavioral and utilization factors related to inadequate screening - Mamon, Joyce A.; Shediac, Mona C.; Crosby, Coral B.; Sanders, Bruce; Matanoski, Genevieve M.; Celentano, David D. (Preventive medicine, 1990)
This study investigated the relationships between health care utilization, knowledge, attitudes, sociodemographic characteristics, and adequacy of cervical cancer screening among a random sample of women from inner-city neighborhoods with high rates of cervical cancer mortality. Of 416 women interviewed, 30.3% reported hysterectomies; women with intact uteri ( N = 290) are the subjects of this analysis. Over two-fifths (44.1%) reported not receiving adequate Pap testing during the previous 4 years. Compared with adequately screened women, they were more likely to be 45 years or older, have no medical insurance, report never having been to an obstetrician-gynecologist, recall never having been told by a medical provider how often to get a Pap test, rely on providers for adequate screening, report not seeking care as often as they think they should, have less knowledge of risk factors for cervical cancer, and believe that women should get Pap tests less than yearly. Separate models for younger and older women showed that these factors vary by age, demonstrating the need for interventions to be sensitive to age subgroups. These findings suggest that cancer control activities should place more emphasis on motivating women as well as influencing the health care delivery system to maximize reductions in cervical cancer.